Managing English Language Teaching Media in a Mobile Phone-Banned Classroom - Putri, Nurul Hanifah; Hanafi, M.; Adriana, Dina (Universitas Sang Bumi Ruwa Jurai, 2025)
This study focuses on how the teacher manages learning media in English classes by comparing the teacher's reflective practices and the contents of teaching modules as official guides. The background of this study departs from the gap between the creativity of the teacher in the classroom and the administrative approach that is reflected in the learning documents. This study uses a qualitative case study design to describe in depth the practice of learning media management in schools. The data collected through in-depth interviews with teacher and document analysis of teaching modules. These two types of data used thematic analysis by applying triangulation methods to ensure the validity of the findings and reinforce the interpretation of the results. The results show that teacher actively choose and modify the media to be more interesting and in accordance with the ability of students, while also preparing alternatives when faced with technical obstacles. In contrast, the teaching module displays only standard media without reflection on their effectiveness or barriers to use. These findings indicate that teacher practice is more innovative than the content of teaching modules that are procedural. The research discussion emphasizes the need to integrate teacher's practical reflections into learning documents so that planning becomes more adaptive, contextual, and responsive to student needs.